Menelaah Simbolisme Dan Makna Cinta Dalam Syair “Mu’allaqat” Karya Imru’ Al-Qais - Adisti Putri Aryani; Ilfina Muttaqwiyatul Qudsiyyah; Muhammad Ilham Wijaya (PT. Hasba Edukasi Mandiri, 2025)
This study aims to explore the symbolism and meaning of love in the poem Mu’allaqat by Imru’ al-Qais, one of the greatest poets in pre-Islamic Arabic literature. Using a qualitative approach with a library research method, this research analyzes the original Arabic text and relevant scholarly sources to uncover how love is represented through diction and poetic symbols. The findings indicate that love in Imru’ al-Qais’ poetry is portrayed as an all-encompassing emotional experience, filled with longing, sacrifice, and existential reflection. Natural symbols such as winds, traces of the camp, tears, and journeys of separation reinforce the image of love as an integral part of the human life cycle. The chosen diction such as